2014
DOI: 10.1177/0047287513517423
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Remoteness and Isolation in the Rural Accommodation Rental Price among Eastern and Western Destinations

Abstract: Experiencing the context of a rural environment is the fundamental aspect of rural travel. In order to estimate quantitative influences of the rural environment, this paper proposes to proxy rurality through two indicators: isolation and remoteness. The estimation of a hedonic pricing model with the use of both Geographic Information Systems and spatial econometrics allows obtaining the specific influence of these factors on rural lodging room prices. The methodology is applied to two tourist destinations with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 64 publications
0
16
0
1
Order By: Relevance
“…Thus, the price of a hotel room is based not only on the characteristics of the hotel site, such as the hotel's size, age, class, and service quality (i.e., site attributes), but also on the characteristics of the location, such as the proximity to downtown, highways, tourist attractions, and airports (i.e., situation attributes). Multiple empirical studies employing different HPMs have indicated that the key determinants of hotel room prices include the hotel's star rating (Bull, 1994;Israeli, 2002;Latinopoulos, 2018;Zhang et al, 2011a), age (Bull, 1994;Zhang et al, 2011a), size De La Pena, Nunez-Serrano, Turrion, & Velazquez, 2016;Hung, Shang, & Wang, 2010;Lee & Zhang, 2012;Soler & Germar, 2018;Zhang et al, 2011a), class (Zhang et al, 2011b), service quality (Monty & Skidmore, 2003;Thrane, 2007;Zhang et al, 2011b), and proximity to tourist attractions (Carvell & Herrin, 1990;Santana-Jiménez, Sun, Hernandez, & Suarez-Vega, 2015;Zhang et al, 2011a), downtown (Bull, 1994;Lee & Jang, 2011;Soler & Gemar, 2018), airport (Lee & Zhang, 2011;Soler & Gemar, 2018), and transportation stations (Thrane, 2007;Zhang et al, 2011a).…”
Section: Hedonic Pricing Approach In the Hotel Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the price of a hotel room is based not only on the characteristics of the hotel site, such as the hotel's size, age, class, and service quality (i.e., site attributes), but also on the characteristics of the location, such as the proximity to downtown, highways, tourist attractions, and airports (i.e., situation attributes). Multiple empirical studies employing different HPMs have indicated that the key determinants of hotel room prices include the hotel's star rating (Bull, 1994;Israeli, 2002;Latinopoulos, 2018;Zhang et al, 2011a), age (Bull, 1994;Zhang et al, 2011a), size De La Pena, Nunez-Serrano, Turrion, & Velazquez, 2016;Hung, Shang, & Wang, 2010;Lee & Zhang, 2012;Soler & Germar, 2018;Zhang et al, 2011a), class (Zhang et al, 2011b), service quality (Monty & Skidmore, 2003;Thrane, 2007;Zhang et al, 2011b), and proximity to tourist attractions (Carvell & Herrin, 1990;Santana-Jiménez, Sun, Hernandez, & Suarez-Vega, 2015;Zhang et al, 2011a), downtown (Bull, 1994;Lee & Jang, 2011;Soler & Gemar, 2018), airport (Lee & Zhang, 2011;Soler & Gemar, 2018), and transportation stations (Thrane, 2007;Zhang et al, 2011a).…”
Section: Hedonic Pricing Approach In the Hotel Industrymentioning
confidence: 99%
“…Although several studies have addressed spatial dependence using spatial econometric models to model hotel room prices (e.g., Lee and Jang, 2011;Santana-Jiménez et al, 2015;Zhang et al, 2011a), only a few studies (e.g., Zhang et al, 2011a;Latinopoulos, 2018;Soler & Germar, 2018) have simultaneously examined both spatial dependence and spatial heterogeneity in HPMs. Furthermore, these studies mainly focused on identifying local variations between room prices and hotel attributes without providing substantial location-based room pricing strategies.…”
Section: Traditional Hpms and Spatial Effectsmentioning
confidence: 99%
“…In rural and low-income countries and regions that previously have relied heavily on agriculture and natural resource extraction, modern tourism provides the dual advantages of generating employment and income while also promoting local cultural heritage and traditions (WTTC 2012). That is, rural lodging establishments improve the quality of life and contribute to the economic rehabilitation of rural areas, because they help decrease underemployment in the rural sector and increase family incomes (Fotiadis, Vassiliadis, and Piper 2014; Hernández-Maestro and González-Benito 2013; Park, Doh, and Kim 2014; Santana-Jiménez et al 2015).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Under the hedonic price model, hotel rooms are considered as heterogeneous products whose prices are affected by a bundle of attributes and characteristics which extent beyond the hotel physical building to include other spatial features. Many studies that employ HPM highlight the factors of room prices such as star rating (Latinopoulos 2018 ), class (Ziqiong et al 2011 ), service quality (Thrane 2007 ), age (Zhang et al 2011 ), size (de la Peña et al 2016 ; Soler and Gemar 2018 ), proximity to airports (Soler and Gemar 2018 ), tourist attractions (Santana-Jiménez et al 2015 ), downtown (Lee and Jang 2012 ) and transportation stations (Zhang et al 2011 ).…”
Section: Literature Reviewmentioning
confidence: 99%